Pengaruh Metode Diskusi Mengangkat Kearifan Lokal Desa Pelangas Terhadap Karakter Disiplin Siswa Kelas IV Materi Keberagaman Budaya di Sekolah Dasar - Apriansyah, Wahyu; Yuanita; Yurdayanti (JBES (Journal Basic Education Skills), 2024)
This research was motivated by the low level of discipline in elementary school students. The aim of the problem in this research is to find out whether the discussion method highlighting the local wisdom of Pelangas Village has an effect on the formation of the disciplined character of fourth grade students regarding cultural diversity in elementary schools. The type of research used is quantitative research with a Quasi Experimental Design experimental method with a Nonequevalent Control Group Design pattern. The sampling technique in this research used the Purposive Sampling technique. The sample for this research was 16 class IV students at SDN 10 Simpang Teritip (experiment) and 16 class IV students at SDN 02 Simpang Teritip (control). The data collection technique used was a test in the form of a questionnaire with 14 statements. The data analysis technique used is normality, homogeneity and hypothesis testing using the independent t-test (polled variance). The research results showed that there was a significant influence on the disciplinary character of students in elementary schools between the experimental and control classes. This is shown in the results of hypothesis testing using the Independent Sample t-test. It can be obtained tcount > ttable, namely tcount of 3.452 while ttable is 2.042, so it can be concluded that the Ha hypothesis is accepted or the discussion method highlights the local wisdom of Pelangas Village in learning and has an influence on the disciplinary character of students in elementary school.